Semantic of Case Particles Ni, De, E, and O as Locative Marker - Alifah, Rahma Fitri (Faculty of Humanities, Diponegoro University, 2023)
This study discusses kakujoshi ni, de, e, and o as markers of location in Japanese sentences. How does the semantic difference of the particle as a locative marker, whether the particles can replace each other in their use, and what is the meaning of the sentence if there is a dropping of the locative marker case particles. This research uses descriptive-qualitative methodology and a note-taking technique. The conclusion from this research is that although the particles ni, de, e, and o are locative markers in sentences, their meaning is different. The particle ni is marker of existence, purpose, and direction, and the verbs that follow are henka doushi and joutai doushi. “De” particle as a locative marker for the activities carried out, mostly followed by dousa doushi. The particle “e” is a marker of purpose and direction and is followed by henka doushi. Particle “o” as a marker of starting point and place that is passed and followed by henka doushi and dousa doushi. There are some particles that substitute one another, such as “ni” and